2008
DOI: 10.1101/lm.1094208
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory in the Morris water maze and activation of cyclic AMP response element-binding (CREB) protein within the mouse hippocampus

Abstract: We investigated the spatio-temporal dynamics of learning-induced cAMP response element-binding protein activation/phosphorylation (pCREB) in mice trained in a spatial reference memory task in the water maze. Using immunohistochemistry, we examined pCREB immunoreactivity (pCREB-ir) in hippocampal CA1 and CA3 and related brain structures. During the course of spatial learning over Days 1-9, pCREB-ir progressively increased in hippocampal neurons whereas its level in the dorsal striatum decreased. No significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 67 publications
4
41
1
1
Order By: Relevance
“…In agreement with our previous observations (Porte et al, 2008b), spatial reference training evoked a biphasic increase in pCREB at 15 min and 8 h post-training time points (vs. 60 min: Ps < 0.01; Fig. 4A for Day 9).…”
Section: Immunohistochemical and Western Blots Analysessupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our previous observations (Porte et al, 2008b), spatial reference training evoked a biphasic increase in pCREB at 15 min and 8 h post-training time points (vs. 60 min: Ps < 0.01; Fig. 4A for Day 9).…”
Section: Immunohistochemical and Western Blots Analysessupporting
confidence: 91%
“…Memory formation and persistence require multiple waves of transcription and translation (Igaz et al, 2002;Dudai and Eisenberg, 2004;Bekinschtein et al, 2007Bekinschtein et al, , 2008; Slipczuk et al, 2009;Katche et al, 2010). In accordance with this, we and others have previously demonstrated that consolidation of hippocampal-dependent, contextual and spatial, LTM formation relies on at least two waves of CREB activation, one just after learning and the other between 3 and 9 h posttraining (Bernabeu et al, 1997;Cammarota et al, 2000;Stanciu et al, 2001;Trifilieff et al, 2006;Martel et al, 2007;Porte et al, 2008b). Furthermore, we also found that alteration of the early CREB phosphorylation in CA1 correlates with spatial memory impairments during normal aging (Porte et al, 2008a).…”
Section: Introductionsupporting
confidence: 57%
“…Collectively, these data position miR-212/132 among a number of other CREB-regulated genes that are required for learning and memory formation (Hall et al 2001;Colombo et al 2003). Indeed, CREB-dependent transcription is induced following an array of learning paradigms and is required for normal cognitive function (Impey et al 1998;Mizuno et al 2002;Porte et al 2008). Nevertheless, while moderate increases in CREB activity facilitate learning, chronic enhancement of CREB-dependent transcription impairs cognitive capacity, paralleling the learning phenotypes observed in tTA::miR-132 animals (Viosca et al 2009;Hansen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…After completion of the last training session, the brains of mice were removed to assess learning-induced brain regional expression of pCREB (Martel et al, 2006;Porte et al, 2008) and c-Fos (Colombo et al, 2003). Under anesthesia, animals were perfused transcardially with an ice-cold solution of 4% paraformaldehyde in phosphate buffer (0.1 M) pH 7.4.…”
Section: Immunochemistrymentioning
confidence: 99%